Management of Public Health: some reflections - Amezcua Viedma, Cesáreo (Razón y fe, 2018)
Outsourcing is a phenomenon that began in private companies and has now reached the public. There is a misunderstanding in confusing outsourcing with privatization. In this paper we approach the debate on public or private management through the prism of the phenomenon of change. The changes question and challenge the traditional system of organization of the Services. Hence the emergence of new forms of management.